The Effect of Profitability, Liquidity, Leverage, Firm Size and Firm Age on Sustainability Report: Evidence from Energy and Healthcare Companies Listed on The Indonesia Stock Exchange - Suroso, Audrey Felicia; Sufiyati, Sufiyati (INOVASI, 2025)
Sustainability reporting has gained increasing importance as companies face growing environmental, social, and governance expectations, particularly in sectors with substantial social and environmental impacts such as energy and healthcare. However, empirical evidence regarding the financial and organizational determinants of sustainability report disclosure in Indonesia remains inconclusive. This study aims to examine the effect of profitability, liquidity, leverage, firm size, and firm age on sustainability report disclosure among energy and healthcare companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a purposive sampling approach, 44 companies were selected, resulting in 132 firm-year observations. The data were analyzed using multiple linear regression with SPSS. The results indicate that profitability and firm size have a positive and significant influence on sustainability report disclosure, suggesting that financially strong and larger firms are more inclined to provide broader sustainability information to meet stakeholder expectations. In contrast, liquidity, leverage, and firm age show no significant effect, indicating that short-term financial capacity, capital structure, and corporate longevity do not necessarily drive sustainability disclosure practices. These findings contribute to the sustainability reporting literature by clarifying the role of firm characteristics within the Indonesian context.